Systematic Review of Integration of Local History in History Education in Indonesia Based on Learning Technology - Asyrul Fikri; Almasdi Syahza; Zetra Hainul Putra (AL-ISHLAH: Jurnal Pendidikan, 2023)
The study's overarching objective is to examine how learning technology is being used to include local history in Indonesian history classrooms. Well-known for its ability to help students better understand national history by incorporating local perspectives. This research employed a meta-analysis based on a systematic review. The research's journal data was culled from the Scopus and Sinta databases. The research method used is the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method. The author uses this method because the research protocol of the PRISMA method is detailed and complete, which allows for avoiding subjective bias in conducting a literature review. This study only uses a literature review without conducting a direct field study. From the search results of Scopus-indexed articles using publish and perish (2017-2022) with the keywords "local history learning," Sinta indexes eight articles through Google Scholar with the keywords "Local History Learning" 23 articles are obtained. Papers that apply to learning technology-based local history learning have two articles indexed by Scopus and ten articles by Sinta. Technology-based learning is a must in learning history to face globalisation in the era of society 5.0. Thus, technology-based learning of local history makes learning history more meaningful, effective, and efficient. Limitations of research on the articles used are only Scopus indexed using publish and perish (2017-2022) and indexed Sinta. So, in the future, it can be updated by analysing articles that contain new research results.